Study of malignant germ cell tumors with special reference to malignant ovarian germ cell tumors: 5 years experience (Journal of Pathology of Nepal, 2012)
Background: Germ cell tumors are rare and complex group of heterogenous neoplasms that comprise both benign and malignant histology. The testes and ovaries are the most common sites. This descriptive study focused on distribution of malignant germ cell tumors with more detail study of ovarian malignant germ cell tumors.Materials and Methods: All cases of malignant germ cell tumor reported from department of pathology of Tribhuvan University Teaching Hospital over five years from April 2007 to April 2012 were included in the study.Results: Thirty five cases (24 female and 11 male) were diagnosed as having malignant germ cell tumors. Most patients were below 30 years of age. Ovary was the most common site followed by testes. Malignant ovarian germ cell tumor comprised 54.3% of all malignant germ cell tumors. Age of these patients ranged from 6 years to 32 years. Most common histologic type was yolk sac tumor.Conclusion: Malignant germ cell tumors can be seen in any age group from new born to old age. However malignant ovarian germ cell tumors occur mainly in first three decades of life, are mostly unilateral and are of large size at the time of diagnosis due to rapid growth. However these tumors are often of low stage and managed with conservative surgery.Journal of Pathology of Nepal (2012) Vol. 2, 289-292DOI: http://dx.doi.org/10.3126/jpn.v2i4.6880